Keterkaitan Tingkat Pengetahuan Dengan Sikap Ibu Hamil Terhadap Pelaksanaan Senam Hamil - Moh Alimansur; Putri Rohmawati (Jurnal Keperawatan, 2014)
Pregnant woman will have the real change of the body that is fit to foetus growth and it will have various sight. Pregnancy gymnastic will be obstained a hale and healthy body and also it can prevent the launch maternal lessening the risk of child birth (85%) maternal pervaginam without complication and yield (98%) birth live the baby with apgar normal.The research design used in this research is approach of cross sectional. The population in this research is pregnant mother in Puskesmas Sukorame, Bujel Kediri. There are 36 people. By using simple random sampling. It is obstained 33 sample of pregnant mother. The obstained variable is analyzed by using data analysis of Kendall Tau. The result of this research shows the knowledge of pregnant mother about pregnancy gymnastic is good enough (52%) the attitude of pregnant mother to pregnancy gymnastic by enough support is 68 %. Based on the statistic test of Kendall Tau is obstained the significant amount P = 0,039 and the correlation coeffisient = 0,407.From the analyzed result known that there is relationship between the knowledge with the attitude of pregnant mother to pregnancy gymnastic. That’s why it is hoped the paramedic to give counseling and also hold the practice of pregnancy gymnastic so it can improve the knowledge of pregnant mother.